RNA-seq analysis reveals transcriptome reprogramming and alternative splicing during early response to salt stress in tomato root - Gan, Jianghuang; Qiu, Yongqi; Tao, Yilin; Zhang, Laining; Okita, Thomas W.; Yan, Yanyan; Tian, Li (Frontiers in Plant Science, 2024)
Salt stress is one of the dominant abiotic stress conditions that cause severe damage to plant growth and, in turn, limiting crop productivity. It is therefore crucial to understand the molecular mechanism underlying plant root responses to high salinity as such knowledge will aid in efforts to develop salt-tolerant crops. Alternative splicing (AS) of precursor RNA is one of the important RNA processing steps that regulate gene expression and proteome diversity, and, consequently, many physiological and biochemical processes in plants, including responses to abiotic stresses like salt stress. In the current study, we utilized high-throughput RNA-sequencing to analyze the changes in the transcriptome and characterize AS landscape during the early response of tomato root to salt stress. Under salt stress conditions, 10,588 genes were found to be differentially expressed, including those involved in hormone signaling transduction, amino acid metabolism, and cell cycle regulation, were greatly enriched in these differentially expressed genes (DEGs).More than 700 transcription factors (TFs), including members of the MYB, bHLH, and WRKY families, potentially regulated tomato root response to salt stress. AS events were found to be greatly enhanced under salt stress, where exon skipping was the most prevalent event. There were 3709 genes identified as differentially alternatively spliced (DAS), the most prominent of which were serine/threonine protein kinase, pentatricopeptide repeat (PPR)-containing protein, E3 ubiquitin-protein ligase. More than 100 DEGs were implicated in splicing and spliceosome assembly, which may regulate salt-responsive AS events in tomato roots. This study uncovers the stimulation of AS during tomato root response to salt stress and provides a valuable resource of salt-responsive genes for future studies to improve tomato salt tolerance.